Metal aerogel and preparation method and application thereof
Patent Information
- Application Number
- CN202311843858.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-12-29
AI Technical Summary
然而,因超滤离心管价格昂贵,采用超滤离心步骤会大大提高制备成本,且该步骤本身耗时甚久;还有研究者使用低介电常数的乙醇作为溶剂加速反应体系的去稳定化过程,从而将钯、铂、金、银、铜、钴湿凝胶的合成时间缩短为30min
[0027]本发明的有益效果为:本发明提供的一种金属气凝胶的制备方法制备所需时间较短且不会给材料结构带来不利影响,制备出的金属气凝胶的性能也较好,该法无需提高反应温度,因此能耗较少;亦无需使用高浓度的金属盐前体或纳米粒子前体,因此可避免成本较高的超滤离心等步骤,因此成本较低。该法通过从各类中低浓度的金属前体(<5mmol/L)出发获得金属气凝胶,通过扰动加快凝胶形成速率,实现了金属凝胶的快速制备。同时该法拓宽了可选的反应物种类范围,可用于制备多种金属气凝胶,其化学组成包括但不限于铁(Fe)、钴(Co)、镍(Ni)、铜(Cu)、铅(Pb)、金(Au)、银(Ag)、铂(Pt)、钯(Pd)等金属中的一种或多种。
Smart Images

Figure CN117717979B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aerogels, specifically to a metal aerogel, its preparation method, and its applications. Background Technology
[0002] Aerogels are porous materials with a three-dimensional network structure and a large specific surface area, and their excellent properties have attracted widespread attention. The preparation of aerogels typically involves two steps: preparing a wet gel and drying the wet gel using a special method. The most traditional method for preparing wet gels is the sol-gel method. The wet gel produced by the sol-gel method is somewhat similar to jelly, and further drying of the wet gel yields the aerogel. Due to surface tension, under normal conditions, the evaporation of the liquid within the gel will cause the fragile gel framework to collapse. Freeze-drying technology can solve this problem. Therefore, freezing the wet gel at a low temperature and then drying it under vacuum conditions yields the aerogel.
[0003] With advancements in sol-gel technology and drying methods, various types of aerogels, such as metal oxide aerogels, polymer aerogels, carbon aerogels, two-dimensional material aerogels, and metal aerogels, have emerged. Among them, metal aerogels combine the unique photoelectric, electromagnetic, and catalytic physicochemical properties of metals with the large specific surface area, porosity, and self-supporting structure of aerogels. They possess high-speed mass transfer channels, highly conductive three-dimensional networks, and unique optical properties, indicating that metal aerogels have enormous application potential.
[0004] Existing methods for preparing metal aerogels suffer from the problem of excessively long preparation times for wet metal gels. To obtain a complete gel, the reaction is typically carried out in an aqueous phase, which hinders diffusion and slows reaction kinetics, resulting in wet gel formation often taking several days to weeks. To address this issue, the following three methods have been attempted:
[0005] One approach is to increase the reaction temperature. For example, some researchers have conducted the reaction at 60°C, which shortened the gelation time of the binary metal gel of copper and palladium, gold, and platinum to 6 hours. However, this method is not only energy-intensive, but it also affects the micro-nano structure.
[0006] Secondly, high concentrations of metal salt precursors or nanoparticle precursors are used, that is, the reaction process is accelerated by increasing the concentration of reactants. For example, some researchers have used ultrafiltration centrifugation to concentrate palladium nanoparticles (metal atom concentration c). M =17mmol / L), and then Ca 2+Palladium hydrogels can be synthesized by inducing electrostatic assembly, with preparation times as short as 5 minutes. However, the high cost of ultrafiltration centrifuge tubes significantly increases the preparation cost, and this step itself is very time-consuming. Other researchers have used ethanol, with its low dielectric constant, as a solvent to accelerate the destabilization process of the reaction system, thereby shortening the synthesis time of palladium, platinum, gold, silver, copper, and cobalt wet gels to 30 minutes. However, this method requires a high concentration of metal precursors (>6 mmol / L), and the use of a single organic solvent limits the types of metal precursors that can be used, as many inorganic metal salts are insoluble in organic solvents, and self-supporting gels cannot be obtained.
[0007] In summary, to reduce the preparation time required for preparing wet metal aerogels, high-concentration precursors or high temperatures must be used. However, these methods will have an adverse effect on the material structure and will also increase energy consumption and preparation costs. Therefore, it is not possible to obtain non-noble metal aerogels with self-supporting structures relatively quickly using existing metal aerogel preparation methods. Summary of the Invention
[0008] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing a metal aerogel that requires less preparation time and does not adversely affect the material structure, as well as the metal aerogel prepared by this method and its application.
[0009] The technical solution adopted by this invention to solve its technical problem is as follows: A method for preparing a metal aerogel provided by this invention includes the following steps:
[0010] (1) Add a metal salt to mixed solvent A, mix well, then add a reducing agent and an initiator in sequence, mix well, and obtain mixed solution B;
[0011] Wherein, the mixed solvent A includes pure water and an organic solvent with a dielectric constant lower than that of water and miscible with water, and the volume fraction of the organic solvent in the mixed solution B is 0-30%;
[0012] The concentration of the metal salt in the mixed solution B is 0.2–5 mmol / L, and the metal salt is one or a mixture of several of the following: ferric chloride hexahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, copper chloride, lead nitrate, chloroaurate trihydrate, silver nitrate, potassium tetrachloropalladate, and potassium chloroplatinate.
[0013] The molar ratio of the reducing agent to the metal salt is (2-20):1;
[0014] The molar concentration of the initiator in mixed solution B is 0–100 mmol / L;
[0015] (2) A disturbance is applied to the mixed solution B, and the mixture is allowed to stand until the black gel is deposited at the bottom of the container or floats on the surface of the solution to obtain the wet metal gel C;
[0016] (3) Wash the wet metal gel C with pure water, then exchange the solvent with tert-butanol, and then freeze it to obtain frozen sample D;
[0017] (4) Freeze-dry frozen sample D to obtain metal aerogel.
[0018] Furthermore, in step (1) above, the organic solvent with a dielectric constant lower than that of water and miscible with water is one or a mixture of methanol, ethanol, acetone, dimethylformamide, and tetrahydrofuran.
[0019] Furthermore, in step (2) above, the reducing agent is sodium borohydride or potassium borohydride.
[0020] Furthermore, in step (2) above, the initiator is sodium hydroxide, potassium chloride, ammonium fluoride or dopamine.
[0021] Furthermore, the disturbance in step (3) above is magnetic stirring or vortex stirring, and the disturbance time is 10s to 5min.
[0022] Furthermore, in step (4) above, the number of washing cycles is 2 to 10, and the total washing time is 1 to 3 days; the number of solvent exchanges is 2 to 4, and the total exchange time is 1 to 3 days.
[0023] Furthermore, in step (4) above, quick freezing is performed using liquid nitrogen, with a quick freezing temperature of 77K and a quick freezing time of 2 to 15 minutes.
[0024] Furthermore, in step (5) above, the freeze-drying temperature is -80℃, the pressure is 1 to 10 Pa, and the drying time is 4 to 48 hours.
[0025] The present invention also provides a metal aerogel, which is prepared by the above-described method for preparing a metal aerogel.
[0026] The present invention also provides an application of a metal aerogel, wherein a metal aerogel prepared by the above-described method can be used as a catalyst for the oxygen evolution reaction.
[0027] The beneficial effects of this invention are as follows: The method for preparing metal aerogels provided by this invention requires a short preparation time and does not adversely affect the material structure. The prepared metal aerogels also exhibit good performance. This method does not require increasing the reaction temperature, thus consuming less energy; it also does not require the use of high-concentration metal salt precursors or nanoparticle precursors, thus avoiding costly steps such as ultrafiltration and centrifugation, resulting in lower costs. This method obtains metal aerogels from various low-to-medium concentration metal precursors (<5 mmol / L) and accelerates the gel formation rate through perturbation, achieving rapid preparation of metal aerogels. Simultaneously, this method broadens the range of selectable reactants and can be used to prepare various metal aerogels, whose chemical composition includes, but is not limited to, one or more of the following metals: iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), lead (Pb), gold (Au), silver (Ag), platinum (Pt), and palladium (Pd).
[0028] The metal aerogel provided by this invention can serve as a catalyst for the oxygen evolution reaction (OER). Currently, most power energy relies on non-renewable resources such as coal and natural gas. Water electrolysis, however, utilizes electricity obtained from renewable energy sources to electrolyze water into hydrogen and oxygen, thus obtaining a clean, high-calorific-value chemical energy substance (i.e., hydrogen). However, this method is not yet suitable for large-scale use due to the very slow kinetics of the anodic OER, which reduces the overall efficiency of water electrolysis. Therefore, researchers have been seeking efficient and stable OER catalysts. Commercial OER catalysts are mainly ruthenium-based (such as ruthenium dioxide (RuO2) and ruthenium / carbon) and iridium-based (such as iridium dioxide (IrO2) and iridium / carbon) catalysts, which are not only expensive but also lack the required activity and stability. The metal aerogel prepared in this invention can be used as an OER catalyst. This invention enables the efficient and low-cost preparation of metal aerogels, which can be used as OER catalysts with significantly better performance than commercial RuO2 catalysts. Furthermore, the main components of the metal aerogel can be non-precious metals, greatly reducing raw material costs. Attached Figure Description
[0029] Figure 1 These are photographs of the process of preparing Example 2 under conditions of stirring and without stirring;
[0030] Figure 2 The spectra are obtained by monitoring the absorbance of the solution during the gelation process of Example 2 under conditions of stirring and no stirring using ultraviolet-visible spectroscopy.
[0031] Figure 3 These are scanning electron microscope (SEM) images of Examples 3, 4, 5, and 6;
[0032] Figure 4This is the elemental distribution map of Example 6 obtained from scanning electron microscopy-X-ray energy dispersive spectroscopy (SEM-EDS).
[0033] Figure 5 This is a comparison of the polarization curves of the electrocatalytic oxygen evolution reaction of Example 7 and commercial RuO2. Detailed Implementation
[0034] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0035] The pure water mentioned in this instruction manual refers to deionized water, ultrapure water, or distilled water.
[0036] The reaction temperature range for the following embodiments is 5–35°C.
[0037]
Example 1
[0038] (1) Add 25 μL of 20 mmol / L chloroauric acid trihydrate and 25 μL of 20 mmol / L nickel chloride hexahydrate to 4.41 mL of mixed solvent A, mix well, add 40 μL of 100 mmol / L sodium borohydride solution and 0.5 mL of 1 mol / L sodium hydroxide solution, mix well to obtain mixed solution B;
[0039] The mixed solvent A consists of 3.41 mL of deionized water and 1 mL of ethanol, and the volume fraction of ethanol in the mixed solution B is 20%.
[0040] The concentration of the metal salt in mixed solution B is 0.2 mmol / L;
[0041] The molar ratio of reducing agent to metal salt is 4:1;
[0042] The molar concentration of the initiator in mixed solution B is 100 mmol / L;
[0043] (2) Stir the mixed solution B magnetically for 1.5 min. While stirring, adjust the speed so that the vortex reaches the middle of the solution. Let it stand for 8 min. The black gel is deposited at the bottom of the container, and the metal wet gel C is obtained.
[0044] Steps (1) to (3) are all performed at 20°C.
[0045] (3) The wet metal gel C was washed with deionized water 6 times for a total washing time of 1 day. Then, it was solvent exchanged with tert-butanol 4 times for a total exchange time of 1 day. Finally, it was quick-frozen with liquid nitrogen at 77K for 13 min to obtain frozen sample D.
[0046] (4) Freeze-dry the frozen sample D at a pressure of 10 Pa and a temperature of -80 °C for 16 h to obtain AuNi metal aerogel.
[0047]
Example 2
[0048] (1) Add 125 μL of 20 mmol / L nickel chloride aqueous solution and 125 μL of 20 mmol / L copper chloride solution to 3.75 mL of mixed solvent A, mix well, add 1 mL of 100 mmol / L sodium borohydride solution, mix well, and obtain mixed solution B.
[0049] The mixed solvent A includes 3.25 mL of ultrapure water and 500 μL of methanol, and the volume fraction of methanol in the mixed solution B is 10%.
[0050] The concentration of the metal salt in mixed solution B is 1 mmol / L;
[0051] The molar ratio of reducing agent to metal salt is 20:1;
[0052] (2) Mixed solution B was stirred with a vortex stirrer for 2 minutes and allowed to stand for 12 minutes. The black gel floated on the surface of the solution, yielding the wet metal gel C. The preparation process is as follows: Figure 1 As shown, stirring clearly accelerates gel formation.
[0053] At the same time, such as Figure 2 As shown, the absorbance of the solution under stirred and unstirred conditions was monitored using UV-Vis spectroscopy: at 15 min, the absorbance under stirred conditions was significantly lower than that under unstirred conditions, and even lower than that under unstirred conditions at 300 min. These results indicate that stirring has a significant accelerating effect on gel formation and sedimentation.
[0054] Steps (1) to (3) are all performed at 30°C.
[0055] (3) The wet metal gel C was washed 8 times with deionized water for a total washing time of 1 day. Then, it was solvent-exchanged twice with tert-butanol for a total exchange time of 2 days. Finally, it was flash-frozen in liquid nitrogen at 77K for 15 min to obtain frozen sample D;
[0056] (4) Freeze-dry the frozen sample D at a pressure of 10 Pa and a temperature of -80 °C for 14 h to obtain NiCu aerogel.
[0057]
Example 3
[0058] (1) Add 500 μL of 20 mmol / L copper chloride solution and 500 μL of 20 mmol / L lead nitrate solution to 3.6 mL of mixed solvent A, mix well, add 0.4 mL of 1 mol / L potassium borohydride solution, mix well, and obtain mixed solution B;
[0059] The mixed solvent A includes 2.1 mL of distilled water and 1.5 mL of acetone, and the volume fraction of acetone in the mixed solution B is 30%.
[0060] The concentration of the metal salt in mixed solution B is 4 mmol / L;
[0061] The molar ratio of reducing agent to metal salt is 20:1;
[0062] (2) Apply magnetic stirring to the mixed solution B for 2 minutes (adjust the speed to make the vortex reach the middle of the solution), let stand for 15 minutes, and black gel will be deposited at the bottom of the container to obtain metal wet gel C;
[0063] Steps (1) to (3) are all performed at 10°C.
[0064] (3) The wet metal gel C was washed 10 times with deionized water for a total washing time of 2 days. Then, it was solvent-exchanged 4 times with tert-butanol for a total exchange time of 2.5 days. Finally, it was flash-frozen in liquid nitrogen at 77K for 12 min to obtain frozen sample D;
[0065] (4) Freeze-dry the frozen sample D at 10 Pa and -80 °C for 18 h to obtain PbCu aerogel.
[0066] Figure 3 a is a SEM image of the PbCu aerogel obtained in Example 3.
[0067]
Example 4
[0068] (1) Add 250 μL of 20 mmol / L cobalt chloride aqueous solution, 250 μL of 20 mmol / L nickel chloride aqueous solution, and 250 μL of 20 mmol / L copper chloride solution to 4.025 mL of mixed solvent A, mix well, add 225 μL of 1 mol / L potassium borohydride solution, mix well, and obtain mixed solution B.
[0069] The mixed solvent A consists of 2.775 mL of deionized water and 1.25 mL of ethanol, and the volume fraction of ethanol in the mixed solution B is 25%.
[0070] The concentration of the metal salt in mixed solution B is 3 mmol / L;
[0071] The molar ratio of reducing agent to metal salt is 15:1;
[0072] (2) Mix the solution B with a vortex stirrer for 3 min, let it stand for 10 min, and the black gel will deposit at the bottom of the container to obtain the wet metallic gel C.
[0073] Steps (1) to (3) are all performed at 25°C.
[0074] (3) The wet metal gel C was washed 10 times with deionized water for a total washing time of 1 day. Then, it was solvent-exchanged 4 times with tert-butanol for a total exchange time of 1 day. Finally, it was flash-frozen in liquid nitrogen at 77K for 10 min to obtain frozen sample D;
[0075] (4) Freeze-dry the frozen sample D at 10 Pa and -80 °C for 12 h to obtain CoNiCu aerogel.
[0076] Figure 3 b is a SEM image of the CoNiCu aerogel obtained in Example 4.
[0077]
Example 5
[0078] (1) Add 100 μL of 20 mmol / L ferric chloride hexahydrate, 100 μL of 20 mmol / L cobalt chloride hexahydrate, 400 μL of 20 mmol / L nickel chloride hexahydrate, 400 μL of 20 mmol / L copper chloride solution, and 250 μL of 20 mmol / L lead nitrate solution to 3.25 mL of mixed solvent A, mix well, add 0.4 mL of 1 mol / L sodium borohydride solution and 0.1 mL of 1 mol / L potassium chloride solution, mix well to obtain mixed solution B;
[0079] The mixed solvent A consists of 2.5 mL of deionized water and 750 μL of methanol, and the volume fraction of methanol in the mixed solution B is 15%.
[0080] The concentration of the metal salt in mixed solution B is 5 mmol / L;
[0081] The molar ratio of reducing agent to metal salt is 16:1;
[0082] The molar concentration of the initiator in mixed solution B is 20 mmol / L;
[0083] (2) Mixed solution B was stirred with a vortex stirrer for 2 min, and then allowed to stand for 12 min. Black gel was deposited at the bottom of the container, yielding metallic wet gel C.
[0084] Steps (1) to (3) are all performed at 25°C.
[0085] (3) The wet metal gel C was washed 10 times with deionized water for a total washing time of 1.5 days. Then, it was solvent-exchanged 3 times with tert-butanol for a total exchange time of 1 day. Finally, it was flash-frozen in liquid nitrogen at 77K for 15 min to obtain frozen sample D;
[0086] (4) Freeze-dry the frozen sample D at 10 Pa and -80 °C for 14 h to obtain FeCoNiCuPb aerogel.
[0087] Figure 3 c is a SEM image of the FeCoNiCuPb aerogel obtained in Example 5.
[0088]
Example 6
[0089] (1) Add 62.5 μL of 20 mmol / L potassium chloroplatinate solution and 62.5 μL of 20 mmol / L nickel chloride hexahydrate solution to 4.525 mL of mixed solvent A, mix well, add 100 μL of 100 mmol / L potassium borohydride solution and 0.25 mL of 1 mol / L dopamine solution, mix well to obtain mixed solution B;
[0090] The mixed solvent A consists of 3.025 mL of deionized water and 1.5 mL of ethanol, and the volume fraction of ethanol in the mixed solution B is 30%.
[0091] The concentration of the metal salt in mixed solution B is 0.5 mmol / L;
[0092] The molar ratio of reducing agent to metal salt is 4:1;
[0093] The molar concentration of the initiator in mixed solution B is 50 mmol / L;
[0094] (2) Stir the mixed solution B with a vortex stirrer for 4 min, let it stand for 9 min, and black gel will be deposited at the bottom of the container to obtain metal wet gel C.
[0095] Steps (1) to (3) are all performed at 30°C.
[0096] (3) The wet metal gel C was washed 8 times with deionized water for a total washing time of 1.5 days. Then, it was solvent-exchanged 3 times with tert-butanol for a total exchange time of 1.5 days. Finally, it was flash-frozen in liquid nitrogen at 77K for 15 min to obtain frozen sample D;
[0097] (4) Freeze-dry the frozen sample D at 10 Pa and -80 °C for 12 h to obtain PtNi aerogel.
[0098] Figure 3 d is a SEM image of the PtNi aerogel obtained in Example 6.
[0099] Figure 4 The image shows the SEM-EDS elemental distribution of the PtNi aerogel obtained in Example 6. Pt and Ni are roughly uniformly distributed in the image, with an atomic ratio of 6:4.
[0100]
Example 7
[0101] (1) Add 187.5 μL of 20 mmol / L nickel chloride hexahydrate, 50 μL of 20 mmol / L ferric chloride hexahydrate, and 12.5 μL of 20 mmol / L chloroauric acid trihydrate to 4.25 mL of mixed solvent A, mix well, add 500 μL of 100 mmol / L sodium borohydride solution, mix well, and obtain mixed solution B;
[0102] The mixed solvent A consists of 3 mL of deionized water and 1.25 mL of ethanol, and the volume fraction of ethanol in the mixed solution B is 25%.
[0103] The concentration of the metal salt in mixed solution B is 1 mmol / L;
[0104] The molar ratio of reducing agent to metal salt is 10:1;
[0105] (2) Mixed solution B was stirred with a vortex stirrer for 3 min, and then allowed to stand for 13 min. Black gel was deposited at the bottom of the container, yielding metallic wet gel C.
[0106] Steps (1) to (3) are all performed at 15°C.
[0107] (3) The wet metal gel C was washed 6 times with deionized water for a total washing time of 2 days. Then, it was solvent-exchanged 4 times with tert-butanol for a total exchange time of 3 days. Finally, it was rapidly frozen in liquid nitrogen at 77K for 9 min to obtain frozen sample D;
[0108] (4) Freeze-dry the frozen sample D at 10 Pa and -80 °C for 12 h to obtain Ni. 75 Fe 20 Au5 aerogel.
[0109]
Example 8
[0110] (1) Add silver nitrate solution and potassium tetrachloropalladium solution to 3 mL of mixed solvent A, mix well, add sodium borohydride solution and ammonium fluoride solution, mix well to obtain mixed solution B;
[0111] Mixed solvent A includes 3 mL of deionized water;
[0112] The concentration of the metal salt in mixed solution B is 2.6 mmol / L;
[0113] The molar ratio of reducing agent to metal salt is 2:1;
[0114] The molar concentration of the initiator in mixed solution B is 100 mmol / L;
[0115] (2) Mix the solution B with a vortex stirrer for 10 seconds, let it stand for 13 minutes, and the black gel floats on the surface of the solution, thus obtaining the wet metal gel C.
[0116] Steps (1) to (3) are all performed at 15°C.
[0117] (3) The wet metal gel C was washed twice with deionized water for a total washing time of 3 days. Then, it was solvent-exchanged once with tert-butanol for a total exchange time of 3 days. Finally, it was rapidly frozen in liquid nitrogen at 77K for 2 min to obtain frozen sample D;
[0118] (4) Freeze-dry the frozen sample D at 1 Pa and -80 °C for 4 h to obtain Ni. 75 Fe 20 Au5 aerogel.
[0119]
Example 9
[0120] (1) Add nickel chloride hexahydrate, silver nitrate solution, and potassium tetrachloropalladate solution to 4.25 mL of mixed solvent A, mix well, add potassium borohydride solution and ammonium fluoride solution, mix well, and obtain mixed solution B;
[0121] The mixed solvent A includes 3 mL of deionized water, 0.25 mL of dimethylformamide, and 1 mL of tetrahydrofuran. The volume fraction of dimethylformamide in mixed solution B is 5%, and the volume fraction of tetrahydrofuran in mixed solution B is 10%.
[0122] The concentration of the metal salt in mixed solution B is 2.6 mmol / L;
[0123] The molar ratio of reducing agent to metal salt is 11:1;
[0124] The molar concentration of the initiator in mixed solution B is 100 mmol / L;
[0125] (2) Mixed solution B was stirred with a vortex stirrer for 2 min 35 s, and then allowed to stand for 13 min. The black gel floated on the surface of the solution, yielding the wet metallic gel C.
[0126] Steps (1) to (3) are all performed at 15°C.
[0127] (3) The wet metal gel C was washed 6 times with deionized water for a total washing time of 2 days. Then, it was solvent-exchanged 4 times with tert-butanol for a total exchange time of 3 days. Finally, it was rapidly frozen in liquid nitrogen at 77K for 8 min 30 s to obtain frozen sample D;
[0128] (4) Freeze-dry the frozen sample D at 5.5 Pa and -80 °C for 26 h to obtain Ni. 75 Fe20 Au5 aerogel.
[0129]
Example 10
[0130] (1) Add nickel chloride hexahydrate, ferric chloride hexahydrate and potassium chloride platinum chloride to 4.25 mL of mixed solvent A, mix well, add sodium borohydride solution, mix well, and obtain mixed solution B;
[0131] The mixed solvent A includes 3 mL of deionized water, 1 mL of methanol, and 0.25 mL of ethanol. The volume fraction of methanol in the mixed solution B is 15%, and the volume fraction of ethanol in the mixed solution B is 10%.
[0132] The concentration of the metal salt in mixed solution B is 5 mmol / L;
[0133] The molar ratio of reducing agent to metal salt is 20:1;
[0134] (2) Mixed solution B was stirred with a vortex stirrer for 5 minutes and allowed to stand for 13 minutes. The black gel floated on the surface of the solution, yielding the wet metallic gel C.
[0135] Steps (1) to (3) are all performed at 15°C.
[0136] (3) The wet metal gel C was washed 6 times with deionized water for a total washing time of 2 days. Then, it was solvent-exchanged 4 times with tert-butanol for a total exchange time of 3 days. Finally, it was rapidly frozen in liquid nitrogen at 77K for 9 min to obtain frozen sample D;
[0137] (4) Freeze-dry the frozen sample D at 10 Pa and -80 °C for 48 h to obtain Ni. 75 Fe 20 Au5 aerogel.
[0138]
Application Example 1
[0139] This application example 1 uses the Ni obtained in Example 7. 75 Fe 20 A comparison of the catalytic performance of Au5 aerogel and commercial RuO2:
[0140] (1) Add 1.0 mg of catalyst (Ni 75 Fe 20 Au5 aerogel and commercial RuO2 were dispersed in 425 μL isopropanol and 75 μL Nafion (1 wt.%), and sonicated for 30 min to obtain a uniform dispersion.
[0141] (2) Add 20 μL of dispersion to the surface of a clean and dry glassy carbon electrode prepared in advance, let it evaporate at room temperature, and form a film after the solvent evaporates, which can be used as the working electrode.
[0142] (3) Pt sheet and Hg / HgO electrode were used as the counter electrode and reference electrode, respectively. Linear scanning voltammetry was performed in an electrolyte (1 mol / L potassium hydroxide) under argon saturation. The voltage range was 1.2 to 1.8 V vs. RHE and the scan rate was 5 mV / s.
[0143] Figure 5 This is a comparison of polarization curves for the electrocatalytic oxygen evolution reaction of commercial RuO2 in Example 7. The test results show that Ni... 75 Fe 20 Au5 aerogel has a lower onset potential and a higher current density at the same potential, indicating that it has superior catalytic performance.
Claims
1. A method for preparing a metal aerogel, characterized in that, Includes the following steps: (1) Add a metal salt to mixed solvent A, mix well, then add a reducing agent and an initiator in sequence, mix well, and obtain mixed solution B; Wherein, the mixed solvent A includes pure water and an organic solvent with a dielectric constant lower than that of water and miscible with water, and the volume fraction of the organic solvent in the mixed solution B is 0~30%, excluding 0; The concentration of the metal salt in the mixed solution B is 0.2~5 mmol / L, and the metal salt is one or a mixture of several of the following: ferric chloride hexahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, copper chloride, lead nitrate, chloroauric acid trihydrate, silver nitrate, potassium tetrachloropalladate, and potassium chloroplatinate. The molar ratio of the reducing agent to the metal salt is (2~20):1; The molar concentration of the initiator in mixed solution B is 0~100 mmol / L, excluding 0; (2) The mixed solution B is disturbed and allowed to stand to obtain the wet metal gel C; the disturbance is magnetic stirring or vortex stirring, and the disturbance time is 10s~5min; The reaction temperature range for preparing metal aerogels is 5~35°C; (3) Wash the wet metal gel C with pure water, then exchange the solvent with tert-butanol, and then freeze it to obtain frozen sample D; (4) Freeze-dry the frozen sample D to obtain a metal aerogel.
2. The method for preparing a metal aerogel according to claim 1, characterized in that, In step (1), the organic solvent with a dielectric constant lower than that of water and miscible with water is one or a mixture of methanol, ethanol, acetone, dimethylformamide, and tetrahydrofuran.
3. The method for preparing a metal aerogel according to claim 1, characterized in that, The reducing agent in step (2) is sodium borohydride or potassium borohydride.
4. The method for preparing a metal aerogel according to claim 1, characterized in that, The initiator in step (2) is sodium hydroxide, potassium chloride, ammonium fluoride or dopamine.
5. The method for preparing a metal aerogel according to claim 1, characterized in that, In step (4), the number of washing cycles is 2 to 10, and the total washing time is 1 to 3 days; the number of solvent exchanges is 2 to 4, and the total exchange time is 1 to 3 days.
6. The method for preparing a metal aerogel according to claim 1, characterized in that, In step (4), quick freezing is performed using liquid nitrogen at a temperature of 77K for 2-15 minutes.
7. The method for preparing a metal aerogel according to claim 1, characterized in that, In step (5), the freeze-drying temperature is -80℃, the pressure is 1~10pa, and the drying time is 4~48h.
8. A metal aerogel, characterized in that, It is prepared by the method for preparing a metal aerogel according to any one of claims 1 to 7.
9. An application of a metal aerogel, characterized in that, A metal aerogel is prepared by any one of the preparation methods of a metal aerogel according to claims 1 to 7, and used as a catalyst for the oxygen evolution reaction.
Citation Information
Patent Citations
Preparation method of bimetallic PtCu aerogel catalyst for high-activity fuel cell
CN113611885A
Preparation method and application of metal aerogel material
CN113648999A
Preparation method of metal aerogel in-situ growth carbon nanotube
CN116288241A
Preparation method and application of P-doped RhAu aerogel electrolysis water oxygen evolution catalyst
CN117187865A
